Evidenciação das informações ambientais nas demonstrações financeiras das empresas de extração e tratamento de minerais, listadas na BM&FBovespa - Maia, Karla Vanessa Nogueira (2015)
This paper aims to identify the environmental information evidenced in the financial statements from 2011 to 2013 in the companies classified in the extraction segment and treatment of minerals listed on the BM&FBovespa. Descriptive methodology was used with a qualitative approach, in a sample of 11 companies. The results of this study showed that environmental accounting is not used as an information tool in decision-making, however, in the Notes, in the Management Report and in the Sustainability Reports were published declarative environmental information, showing the companies that obtained profit, issued its Sustainability Report and were reported environmental information.